Response Format Effects in Encounter Norm Questions. (26th May 2016) - Vaske, Jerry J.; Donnelly, Maureen P.; Bingül, Meryem Bihter
ABSTRACT: Survey response format has been shown to influence norm prevalence (percentage reporting a norm) and the numerical value of the reported norm. This article summarizes an experiment where respondents were randomly assigned to one of two conditions. In the semi-open response format treatment, respondents ( n = 817) "wrote in a number" for an acceptable number of visitor encounters. In the closed format treatment, individuals ( n = 826) "circled a number" of acceptable encounters along a range of possible responses. Hypothesis 1 predicted that norm prevalence would be higher for the closed format than the semi-open. Hypothesis 2 predicted that the mean tolerance level would differ in the two treatments. Results supported hypothesis 1. The percent reporting a norm was statistically higher in the closed versus the semi-open treatment. Results failed to support hypothesis 2. The average tolerance levels for the closed and semi-open formats were statistically equivalent.